BANK SYARIAH MENURUT PANDANGAN ULAMA KLASIK - Muhammad, Muhammad (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2025)
Islamic banks are modern financial institutions that operate based on the principles of Islamic law, especially the prohibition of usury, gharar, and maisir. Although at the time of classical fiqh scholars there was no banking institution in its current form, the basic concepts they formulated in fiqh muamalah became an important foundation for the development of Islamic banks. Classical scholars such as Abu Hanifah, Malik bin Anas, Shafi'i, and Ahmad bin Hanbal agreed that any addition required in a loan contract is forbidden usury. The thoughts of Ibn Taymiyyah and Al-Ghazali also confirm that money is not a commodity to be traded for interest, but only a medium of exchange that serves to maintain the smooth running of economic activity. Principles such as justice ('adl), mutual consent, transparency, and cooperation in risk and profit formulated by classical scholars have proven to be relevant to the modern Islamic banking system. Through halal contracts such as murabahah, mudharabah, musyarakah, and ijarah, Islamic banks are a fairer and more ethical alternative to conventional banks. This study shows that the thinking of classical scholars remains relevant as a normative and ethical foundation in developing a contemporary financial system with social justice.